1995
DOI: 10.1161/01.cir.91.4.1161
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinemia-Induced Vascular Damage in the Minipig

Abstract: In minipigs, the present methionine-rich caseinate-based diet induced hyperhomocysteinemia, which reproduces the metabolic and histopathological situation found in homocysteic patients. Our results show that hyperhomocysteinemia-induced vascular alterations favor the viscous component of the wall rheology to the detriment of the elastic component. Furthermore, they extend to hyperhomocysteinemia the therapeutic effects characteristically shared by ACE inhibitors in association with hydrochlorothiazide against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(84 citation statements)
references
References 51 publications
2
80
1
1
Order By: Relevance
“…Normally aged skin that has not been chronically exposed to sunlight is characterized by generalized wrinkling, an epidermal layer thickened by regions of hyperkeratosis, thinning of the underlying dermis (Tyner et al, 2002). The alterations of the architecture of the collagen and elastin networks are common features in aging tissues such as skin (Lavker et al, 1986) and arteries (Rosenthal, 1987) and were also observed in arterial tree of a dietary model of hyperhomocysteinemia in minipig (Rolland et al, 1995) and in cerebral arterioles of CBS-deficient mice (Baumbach et al, 2002).…”
Section: Resultsmentioning
confidence: 97%
“…Normally aged skin that has not been chronically exposed to sunlight is characterized by generalized wrinkling, an epidermal layer thickened by regions of hyperkeratosis, thinning of the underlying dermis (Tyner et al, 2002). The alterations of the architecture of the collagen and elastin networks are common features in aging tissues such as skin (Lavker et al, 1986) and arteries (Rosenthal, 1987) and were also observed in arterial tree of a dietary model of hyperhomocysteinemia in minipig (Rolland et al, 1995) and in cerebral arterioles of CBS-deficient mice (Baumbach et al, 2002).…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, macrophage-driven foam cell formation might be increased by the interaction between homocysteine thiolactone and LDL (McCully, 1996;Olszewski and McCully, 1993). Along with the direct activation of matrix metalloproteinase-2 (Bescond et al, 1999), vascular damage might also result from an impairment of the tertiary structure of connective tissue protein, because of the reduced degree of cross-linkage between collagen and fibrin monomers (Lubec et al, 1996a;McCully, 1996;Rolland et al, 1995). A defect in collagen polymerization was reported in homocystinuric patients with severe hyperhomocysteinemia (Lubec et al, 1996a).…”
Section: Hyperhomocysteinemia-mediated Oxidant Stress Through Imbalanmentioning
confidence: 99%
“…Although additional studies are required to clarify the molecular mechanisms responsible for hyperhomocysteinemiainduced vascular disorders, there is evidence that the direct cytotoxicity of markedly elevated homocysteine and/or of its oxidized by-products (homocysteine thiolactone, homocysteine sulfinic acid, and homocysteic acid) damages endothelial cells (Dudman et al, 1991;Starkebaum and Harlan, 1986;Wall et al, 1980). This direct cytotoxicity may also cause alteration in the tertiary structure of proteins in connective tissue and hence affect the vascular wall structure (Lubec et al, 1996a;McCully, 1996;Rolland et al, 1995). Specific disulfide linkage between homocysteine and the sulfhydryl group of an intracellular protein may be an alternative molecular mechanism underlying hyperhomocysteinemia-induced vascular dysfunction.…”
Section: Durand Et Almentioning
confidence: 99%
“…A study in pigs showed that a high methionine diet which produces high serum homocysteine produced elevated PAH [141]. e lung dysfunction in this last study [141] was greatly lowered by an angiotensin-converting enzyme inhibitor, strongly suggesting a role for excessive superoxide in homocysteine-initiated PAH as well.…”
Section: Principlementioning
confidence: 55%